Tolak Ukur Keberhasilan terhadap upaya pemulihan pada Anak Korban Kekerasan Seksual di Panti Sosial Asuhan Anak Balita Tunas Bamgsa - Warda Uswa Tsaniya; Ati Kusmawati (Jurnal Medika Nusantara, 2025)
Crime is a phenomenon that often occurs in society so that it becomes a matter of public discussion both directly and indirectly, such as through social media and print media. The type of violence that occurs against children is dominated by sexual violence, which reached 9,588 cases, where the largest percentage of these cases occurred from the closest environment, namely family and relatives. When acts of sexual violence occur against children, there are impacts such as trauma after the violence occurs. The aim of this research is to determine the efforts, stages and treatment of recovery provided by PSAA Balita Tunas Bangsa to child victims of sexual violence in the orphanage. From the violence received, the impact and trauma experienced by children as a result of sexual abuse causes lasting trauma and can disrupt their activities in socializing with their environment. Based on the impact of violence, there is a need for handling and efforts to be made to resolve it with the parties provided by PSAA Balita Tunas Bangsa with several stages such as; 1). Establishing Safety (Building Safety), 2). Remembrance and Mourning (Memories and Grief), 3). Reconnection (Reconnecting). From the stages of the efforts given, results will be obtained in the form of benchmarks for the success of the recovery efforts that have been given by looking at the victim's progress regarding the trauma obtained from the victim's achievements, the wounds on the victim and the recovery of these wounds, and the victim no longer remembering the things that were done. leading up to the event.